An investigation of growth mechanism of coal derived graphene films. (June 2017) - Vijapur, Santosh H.; Wang, Dan; Ingram, David C.; Botte, Gerardine G.
Graphical abstract: Highlights: Graphene films were successfully synthesized from coal. Coal pyrolysis released hydrocarbon gases act as indirect precursors for graphene domains. Graphene films are formed by merging and growth of individual graphene domains. Abstract: The growth mechanism of coal derived graphene films synthesized via chemical vapor deposition on copper substrates was investigated utilizing Raman spectroscopy, X-ray photoelectron spectroscopy, selected area electron diffraction, optical microscopy, and gas chromatography. The synthesis of coal derived graphene films is a two-step process, wherein the copper in annealed followed by flash pyrolysis of coal under hydrogen environment. The growth mechanism involves a copper catalyzed reaction to produce a carbon film within the first few minutes of synthesis, followed by a hydrogen catalyzed graphitization of the underlying carbon film to form graphene domains which merge together to form graphene films.